Tuning Pressure Drop in Isoporous Membranes: Design with Fabrication Variability. Issue 8 (6th May 2021) - Ong, Shi Ke; Birgersson, Erik; Low, Hong Yee
Abstract: Isoporous membranes consist of well‐defined micro and nanoscale pore architecture comprising uniform pore sizes with straight pore channels. In contrast to traditional random porous membranes with tortuous flow paths, isoporous membranes offer the opportunity to achieve a high degree of membrane customization and low pressure drop. Here, a physics‐based machine learning methodology that enables the predictive design of a single‐layer isoporous membrane in terms of the pressure drop is reported. In short, the methodology consists of a hybrid approach that includes experimental data on the variability of the pore architecture and the resulting pressure drop, training of a neural network with data from validated physics‐based simulations of laminar flow through the membrane, and Monte Carlo simulation (MCS) to stochastically account for the inherent variabilities of the pore architecture of fabricated isoporous membranes. Overall, the neural network and MCS predict the range of Δ p for a given single‐layer membrane well. Experimental values fall within 90% of the minimum and maximum predicted Δ p values. In addition, a sensitivity analysis with MCS is carried out to quantify how design and operating parameters affect the overall pressure drop. The methodology can be extended to membranes comprising multiple layers and to account for filtration efficiency. Abstract : A physics‐based machine learning methodology is developed to enable the predictive design of a single‐layer isoporous membrane in terms of the pressure drop. With a trained neural network, the inherent variability in the pore architecture of fabricated membranes is accounted for through Monte Carlo simulations. Experimental values fall within 90% of the minimum and maximum predicted pressure drop values.